2016
DOI: 10.14260/jemds/2016/184
|View full text |Cite
|
Sign up to set email alerts
|

Optic Disc Edema/Papilledema: A Clinical Profile

Abstract: AIMTo evaluate the clinical profile of patients with disc edema/papilloedema and its pattern in various patients. PURPOSETo evaluate causes of Disc edema/Papilloedema and associated clinical picture. DESIGNProspective Study. METHODThis study is a non-randomized prospective case series being conducted in the patients with disc edema attending OPD and referred from other departments to RIO, Gandhi Medical College and associated Hamidia Hospital, Bhopal from Jan 2013-Sept 2014. Detailed history was taken with spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, the study conducted by Solanki et al . [ 9 ] reported an M: F ratio of 3:4.1 with a female preponderance (56.2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study conducted by Solanki et al . [ 9 ] reported an M: F ratio of 3:4.1 with a female preponderance (56.2%).…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 11 12 ] In contrast, ICSOL was the most common cause of bilateral disc edema in the studies by Solanki et al . [ 9 ] and Vaidya et al . [ 6 ] Five patients with unilateral ODE who were blind had CRVO, nonarteritic AION, and optic neuritis as the respective etiology.…”
Section: Discussionmentioning
confidence: 99%
“…17 Findings of the neuroimaging showed that majority of the patients (70.65%) were suffering from non-space occupying lesions. However, the study of Solanki et al 7 reported that one third of the patients with optic disc edema had non-space occupying lesions. The dissimilarity might be due the fact that their study was conducted in a multidisciplinary hospital and many of their study subjects were referred from the department of neuro-surgery where most of the patients were clinically diagnosed as intracranial space occupying lesion.…”
Section: Methodosmentioning
confidence: 97%
“…A prospective study on disc oedema was done by Solanki et al 5 50 patients in which 42% and 58% were male and female respectively were enrolled for their study. Age group which was affected most commonly 11-20 years.…”
Section: Pathogenesismentioning
confidence: 99%